MHD mixed convective stagnation point flow along a vertical stretching sheet with heat source/sink. (February 2018) - Sharma, P.R.; Sinha, Sharad; Yadav, R.S.; Filippov, Anatoly N.
Highlights: Effect of mixed convection parameter ( λ ) with heat source/sink parameter ( δ ) is studied. Nusselt number increases with increasing mixed convection parameter. Skin friction coefficient increases with increasing mixed convection parameter. Pr shows dual effects on velocity for assisting and opposing flows respectively. δ shows dual effects on velocity for assisting and opposing flows respectively. Abstract: Aim of the paper is to investigate the effects of heat generation/absorption on MHD mixed convective stagnation point flow along a vertical stretching sheet in the presence of external magnetic field. The governing boundary layer equations are formulated and transformed into nonlinear ordinary coupled differential equations using similarity transformation and numerical solution is obtained by using Runge-Kutta fourth order scheme with shooting technique. The effects of various physical parameters such as velocity ratio parameter, mixed convection parameter, Hartmann number, Prandtl number and heat source/sink on velocity and temperature distributions are presented through graphs and discussed numerically. The skin friction coefficientand Nusselt number at the sheet are derived, discussed numerically and their numerical values are presented through tables.